Experimental studies on the pH levels that affect demineralization and remineralization of human tooth enamel. - Sherzad Abdulrahman Muhammad; Bakhtiar Muhialdin Ahmed (Erbil Dental Journal)
Background and Objective: It is thought that demineralization of enamel occurs below pH 5.5. We hypothesize that it also happens at higher levels. Furthermore, the effective pH levels for demineralization and remineralization differ from person to person. The outcome of this study can help in planning new preventive strategies regarding tooth decay. This study aimed to detect the pH levels that influence the demineralization and remineralization of enamel. Methods: Ninety-five participants of one age group (19-34 years old) were involved in this case-control study and divided into a caries-free group, very low-caries group and low-to-moderate caries group by relying on the DMFT value as a criterion for the diagnosis of dental caries. Forty previously extracted caries-free teeth were exposed to buffered saliva samples of the participants from the three groups at 37 oC for 24 hours. The concentration of calcium loosed or gained from the teeth was assessed using a spectrophotometer. A correlation test and regression plot were used for the data analysis. Results: Significant correlations were obtained between the pH levels (4.6 to 7.0) and the demineralization/remineralization of enamel. Moreover, regression plots between the pH and calcium concentrations resulted in new pH points that may play effective roles in thedemineralization and remineralization processes. Conclusion: New pH levels have been obtained regarding demineralization and remineralization of enamel. Responses to fluctuations in these pH levels differ from person to person, which in turn lead to a variation in the incidence and severity of tooth decay.